Epistemology in accounting : a paper ... for the degree of M.B.A. in Accounting and Finance at Massey University - Davey, Howard Baxter (Massey University, 1981)
The aim of the study was to investigate different epistemological approaches to accounting in order to distill the most appropriate methods for the future. All methods of analysis available in either the social or the traditional sciences have been evidenced in accounting, thus there was no need to examine techniques outside the discipline. This study examined and compared five approaches to theory construction and knowledge gathering in accounting as representative of the primary methods of epistemology in accounting. These were:- rules and standard setting, convention derivation, induction and scientific analysis, normative-deductive, and weltanschauung. Having defined the limits of the discipline, the study reviewed each approach analysing their strengths and weaknesses. Conclusions and future methodological prescriptions follow logically from the first sections but are normative in nature. The results indicated that no one method could meet all of the requirements of the discipline, yet empirical research held the most promise for the future. Two further conclusions were made. Firstly, other methods of inquiry may be quite legitimate in certain cases and should be judged on what they offer. Secondly, accounting should now be viewed as a social institution, involving political and social factors in its developmental and theory construction processes as well as in accounting questions per se.
Keywords: Accounting; Methodology